Hubungan Aktivitas Fisik dengan Derajat Hipertensi pada Lansia - Karyatin; Tati Hidayati (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2024)
Non-communicable diseases still contribute to the highest mortality rate in Indonesia, especially hypertension. One of the factors of hypertension is physical activity. WHO also estimates that 1 in 5 women worldwide have hypertension. This number is greater among men, which is 1 in 4 people (Ministry of Health of the Republic of Indonesia, 2023). The purpose of this study was to determine the degree of hypertension, determine physical activity, and analyze the relationship between physical activity and hypertension at the Kenanga Posbindu, Grogol Village. The population of this study was 55 respondents with hypertension. The sample of this study used a purposive sampling technique so that a sample of 34 respondents was obtained. The focus of this study was the incidence of hypertension and physical activity. The analysis used in this study was an analysis using SPSS with the Chi-Square test. The results of the analysis showed that Hypertension with Grade 2 was 52.9% higher than Hypertension with Grade 1, which was 47.1%. Physical activity 52.9% were quite active. There is a significant relationship between physical activity and hypertension (P value = 0.017). The conclusion of this study is that hypertension sufferers who do less physical activity have a 2.31 times greater chance of experiencing grade II hypertension when compared to hypertension sufferers who do light physical activity. This can be caused by other factors such as high physical stress, rest or other lifestyle factors.